Pengaruh Kepemimpinan Transformasional Terhadap Kinerja Karyawan Pada PDAM Sragen - Ningtyas, Dewantika Putri; , Lukman Hakim, SE, M.si (2016)
The purpose of this study were: 1) Determine whether the variable behavior of transformational leadership consists of the influence of the ideal balance of individual, inspirational motivation and intellectual stimulation has an influence on employee performance; 2) Determine which of the variables of transformational leadership consists of charisma, intellectual stimulation, individual attention, and motivation inspiring the most dominant influence. The population in this study were all employees of PDAM Sragen. The sampling technique in this research is purposive sampling or sampling based on the considerations and criteria, in order to obtain a sample of 55 respondents. Methods of data analysis using: 1) test the research instrument, ie test the validity and reliability testing; 2) Test assumptions Classic, namely normality test, multicollinearity, and heteroscedasticity; 3) Test the multiple linear regression; 4) Test the hypothesis, that the t test, F test, and test the coefficient of determination. The results of data analysis showed that: 1) Test questionnaire is valid and reliable; 2) Test the classical assumption, there is no error in the classical assumption; 3) The results of multiple linear regression test showed that the regression coefficient variable intellectual stimulation has the greatest value of the regression coefficient, so the variable intellectual stimulation is the most dominant variable affecting employee performance than other variables; 4) The results of hypothesis testing, the result: a) The results of the t test showed that charisma, intellectual stimulation, individual attention, and motivation inspiration individually significant effect on the performance of employees, this is indicated by the significant value of less than 0.05; b) F test results showed that charisma, intellectual stimulation, individual attention, and motivation inspiration jointly significant effect on the performance of employees, this is indicated by the significant value of less than 0.05; c) determination coefficient test results obtained figures adjusted-R2 of 0.268 or 26.8% means that the variables of transformational leadership is able to explain the variation of the variable performance of employees amounted to 26.8% and the remaining 73.2% is influenced by other variables outside the model studied.